Correlation of clinical characteristics between patients with seasonal influenza and patients infected by the wild type or delta variant of SARS-CoV-2 - Zhang, Jianguo; Huang, Xing; Tao, Zhimin (Frontiers in Public Health, 2022)
Background: We compared clinical characteristics of the coronavirus disease 2019 (COVID-19) patients, infected by wild-type or delta variant of SARS-CoV-2, in connection to those of the seasonal influenza patients, all in mild cases. Methods: We retrospectively studied 245 mild COVID-19 patients and 115 mild COVID-19 patients infected by delta variant of SARS-CoV-2, with their demographic information, medical history, and laboratory data from hospital records, individually compared to 377 mild seasonal influenza patients, before and after individual treatment. Results: Compared to the influenza cohort, the COVID-19 cohort or delta variant COVID-19 cohort demonstrated younger median age, lower male ratio, shorter duration from disease onset to hospitalization. Hypertension remained the top comorbidity among all cohorts. Based on patients’ data upon hospitalization, the correlation of clinical characteristics between the seasonal influenza patients and the wild-type COVID-19 patients is greater than that between the seasonal influenza patients and the delta variant COVID-19 patients. Individual treatment in each viral disease alleviated most hematological parameters, but some compromised biomarkers at the time of hospital discharge revealed persistent renal or myocardial impairment among COVID-19 and influenza patients in recovery. Conclusions: Timely treatment using broad-spectrum antibiotics and antiviral drugs could moderately alleviate the acute viremia in mild COVID-19 and influenza patients, followed by compromised recovery. To prepare for the upcoming flu season amid the COVID-19 pandemic, preventive and adequate immunizations of both flu and COVID-19 vaccines, as well as specific therapeutics to effectively reverse viral impairments, are in urgent need.